Nuclear DNA replication in trypanosomatid protozoa - da Silva, M. S. [UNESP]; da Silveira, R. C.V. [UNESP]; Perez, A. M. [UNESP]; Monteiro, J. P. [UNESP]; Calderano, S. G.; da Cunha, J. P.; Elias, M. C.; Cano, M. I.N. [UNESP] (My University, 2013)
The parasites belonging to the family Trypanosomatidae (order Kinetoplastida) are among the most primitive eukaryotes. Some trypanosomatids are the etiologic agents of neglected human pathologies such as South American and African trypanosomiasis and leishmaniasis. As a consequence of their ancient phylogenetic position, nuclear DNA replication in trypanosomatid protozoa shows conserved and non-conserved features. DNA replication in trypanosomatids initiates nearly simultaneously in the nucleus and in the genetic material of the single mitochondrion (or kinetoplast), suggesting that DNA synthesis is coordinately regulated in both organelles. In eukaryotes, nuclear DNA replication is preceded by assembly of the pre-replication complex, which is coordinated by the Origen Recognition Complex (ORC). However, in trypanosomatids, the prereplication complex differs from other eukaryotes and is similar to Archaea. All of these parasites contain only one protein that recognizes the replication origins and is found in the nucleus throughout the cell cycle, which suggests that it is not involved in the control of replication initiation. In the S phase, DNA replication starts at these origins and, in trypanosomes, occurs mainly at the nuclear periphery. In Leishmania spp., from the beginning up to mid S phase, replication sites are spread throughout the nuclear space to form subnuclear foci of active DNA replication. From mid-to-late S phase, replication is restricted to sites at the nuclear periphery. Few nuclear DNA polymerases have been described in trypanosomatid protozoa, although putative members of all polymerase families are found in their genomes. Structural and functional analyses indicate that most of these polymerases are highly conserved, with some of them being involved in polymerization and the repair of DNA damage. Although there are no descriptions of DNA polymerase δ in these protozoa, one of this protein's partners, proliferating cell nuclear antigen (PCNA), is found in the nucleus throughout the cell cycle. Trypanosomatid PCNA forms distinct subnuclear foci in the S phase, whereas its distribution is more diffuse in the G2/M phase and in post-mitotic phase cells. This finding suggests that there may be phase-specific regulation of PCNA in the cell cycle. DNA replication in trypanosomatid telomeres is terminated by the action of telomerase. The biochemical properties of the trypanosomatid enzyme are conserved and resemble those described in other eukaryotes. Leishmania telomeres replicate late in S phase and at the beginning of G2 phase the chromosomes cluster at the nuclear periphery. Telomerase co-localizes with telomeres from the late S to G2 phases. These observations point to the existence of replication factories in trypanosomatids, the importance of which will be reviewed and discussed in this chapter.© 2012 Nova Science Publishers, Inc. All rights reserved.